The Effect of Surfactant on the Characteristics of Curcumin-Loaded Nanostructured Lipid Carriers: Fluorescence and Stability Study - Mega Nurul Madania; Zubaidah Ningsih; Anastasia Fitria Devi; Diah Mardiana; Ulfa Andayani (The Journal of Pure and Applied Chemistry Research, 2025)
Curcumin, a bioactive compound derived from Curcuma longa, offers significant pharmacological benefits such as antioxidant, anti-inflammatory, and anticancer properties. However, its therapeutic application is restricted due to poor water solubility, low systemic bioavailability, and limited skin penetration. This study explores the use of Nanostructured Lipid Carriers (NLCs) as a drug delivery system to improve curcumin's stability and permeability. Two formulations were developed: NLC-KUR-T80, which encapsulates curcumin using the non-ionic surfactant Tween 80, and NLC-KUR-CTAB, which uses the cationic surfactant CTAB. Both formulations were prepared using the Phase Inversion Temperature (PIT) method and characterized for particle size, polydispersity index (PI), zeta potential, encapsulation efficiency (EE%), and fluorescence properties. Results revealed that CUR-NLC-CTAB exhibited a larger particle size (1410 ± 183 nm), higher zeta potential (78.70 ± 0.67 mV), and significantly better encapsulation efficiency (27.33 ± 3.33%) compared to CUR-NLC-T80. Fluorescence studies demonstrated that curcumin within NLC-CTAB had enhanced fluorescence intensity, indicating better stability and distribution within the lipid matrix.